Dificuldade na laringoscopia e na intubação orotraqueal: estudo observacional - Andrade, Rebeca Gonelli Albanez da Cunha; Lima, Bruno Luís Soares; Lopes, Douglas Kaíque de Oliveira; Couceiro Filho, Roberto Oliveira; Lima, Luciana Cavalcanti [UNESP]; Couceiro, Tania Cursino de Menezes (Elsevier, 2018)
Introduction: Since anesthesia complications associated with unexpected difficult airway are potentially catastrophic, they should be avoided. The modified Mallampati test and jaw‐thrust maneuver enable the identification of difficult airway. The aim of this study was to associate the modified Mallampati test and the jaw‐thrust maneuver with laryngoscopy (Cormack‐Lehane) in an attempt to identify a better predictor of difficult airway in an adult population undergoing elective surgery. Method: A cross‐sectional study in which 133 adult patients undergoing elective surgery requiring tracheal intubation were analyzed. The accuracy and specificity of the modified Mallampati test and jaw‐thrust maneuver were assessed by correlating them with difficult laryngoscopy (Cormack‐Lehane Degrees 3 and 4). Results: In the 133 patients evaluated the difficult intubation rate found was 0.8%; there was association between the two predictive tests proposed (p = 0.012). The values of 94.5% for specificity and 95.4% for accuracy were found for the jaw‐thrust maneuver and for the modified Mallampati test, the values found were 81.1% and 81.2%, respectively. Kappa agreement identified a result of 0.240 between jaw‐thrust maneuver and Cormarck‐Lehane, which was considered reasonable. On the other hand, a poor agreement (κ = 0.06) was seen between modified Mallampati test and Cormarck‐Lehane test. Conclusion: The jaw‐thrust maneuver presented superior accuracy and agreement than the modified Mallampati test, showing the ability to identify a difficult airway. It is necessary to emphasize the association of tests in the evaluation of patients, emphasizing their complementarity to minimize the negative consequences of repeated laryngoscopies.
Difficult laryngoscopy and tracheal intubation: observational study
Keywords: Airway; Difficult airway; Intubation; Jaw‐thrust maneuver; Laryngoscopy; Mallampati test